Anthropometric and mechanical factors determining sprint in young soccer players: a brief report - Alejandro Bustamante-Garrido; Alejandro Bustamante-Garrido; Alejandro Bustamante-Garrido; Esteban Aedo-Muñoz; Esteban Aedo-Muñoz; Ciro Brito; Danilo Silva-Esparza; Jorge Pérez-Contreras; Jorge Pérez-Contreras; Jorge Pérez-Contreras; Mikel Izquierdo-Redin; Hugo Cerda-Kohler; et al. (Frontiers Media S.A., 2024)
Sprint performance is a critical factor in soccer. While previous studies have extensively explored the biomechanical, physiological, and metabolic determinants of sprinting, the impact of anthropometric variables in team sports contexts, especially soccer, remains underexplored. This study aims to investigate the influence of anthropometric and mechanical variables on sprint performance in young soccer players. Fifty-eight young soccer players were evaluated in anthropometry and a 30-meter (m) sprint using radar technology. Split times in 5, 15, and 30 m were determined, in addition to the assessment of the force-velocity profile proposed by Morin and Samozino. Results: Key anthropometric variables associated with improved sprint performance included lower-limb muscle mass at distances 5 and 15 m (R2 = 0.08 and R2 = 0.09, respectively, both with small effects). Additionally, body composition, particularly a lower % body fat, was crucial across all sprint distances (ES: large). Among the mechanical variables, max power (R2 = 0.997, ES: large) and maximum velocity (R2 = 0.553, ES: large) are the mechanical variables that were most strongly associated with sprint performance over distances greater than 30 m. Soccer coaches, athletic trainers, and strength and conditioning specialists working with young athletes can apply the findings of this study to their training programming.